Changes in Soil Available Phosphorus, Leaf Phosphorus Content and Yield of Sword Bean (Canavalia ensiformis (L.) DC.) by Application of SP-36 and Phosphate Rock on Acid Upland Soil of East Lampung - Achmad Arivin Rivaie (JOURNAL OF TROPICAL SOILS, 2015)
A glasshouse trial was performed to determine changes in phosphorus (P) nutrition and the yield of sword bean (Canavalia ensiformis (L.) DC.) following the application of different rates and types of P fertilizer in an acid upland soil of East Lampung. Two different types of P fertilizer, namely SP-36 (total P = 36%) and Phosphate Rock (PR) (total P = 24.3%, particle size distribution = 75% <0.25 mm, 85% < 0.50 mm, 90% < 1.00 mm) were used in the trial. For the treatment, each P fertilizer type consisted of four rates (0, 50, 100 and 150 mg P2O5 kg-1 soil) that were arranged in a Completely Randomized Design with four replications. The results showed that the application of P fertilizers had significant effects on soil pH, soil plant-available P, the potential-P (HCl 25%), leaf N and P concentrations, the yield of sword bean. Increased rates of both forms of P fertilizer increased the soil pH values. As the soil used had low pH and very high exchangeable Al, hence, this result is most probably related to the addition of Ca2+ to the soil solution that resulted from the P fertiliser applied (liming effect), either from SP-36 (monocalcium phosphate) or PR (flour apatite). There was no difference in soil available P concentration due to the different in P fertilizer types, indicating that 4 months after the fertilizer application, the relatively insoluble Phosphate Rock had the same P solubility with SP-36. Increased rates of both forms of P fertilizer increased the sword bean yield. For the application of 0 kg P2O5 ha-1, although sword bean crops had pods, but, they did not give any seed. Whereas, at the addition of P fertilizer at the rate of 50, 100, and 150 kg P2O5 ha-1 for both P fertilizer types, the crops were able to give the seeds in the pods. [How to Cite: Achmad AR. 2015. Changes in Soil Available Phosphorus, Leaf Phosphorus Content and Yield of Sword Bean (Canavalia ensiformis (L.) DC.) by Application of SP-36 and Phosphate Rock on Acid Upland Soil of East Lampung. J Trop Soils 19: 29-36. Doi: 10.5400/jts.2015.20.1.29][Permalink/DOI: www.dx.doi.org/10.5400/jts.2015.20.1.29]